Anthelminthic activity of glibenclamide on secondary cystic echinococcosis in mice. - Julia A Loos; María Sandra Churio; Andrea C Cumino (Public Library of Science (PLoS), 2017)
Cystic echinococcosis (CE) is a worldwide parasitic zoonosis caused by the larval stage of Echinococcus granulosus. Current chemotherapy against this disease is based on the administration of benzimidazoles (BZMs). However, BZM treatment has a low cure rate and causes several side effects. Therefore, new treatment options are needed. The antidiabetic drug glibenclamide (Glb) is a second-generation sulfonylurea receptor inhibitor that has been shown to be active against protozoan parasites. Hence, we assessed the in vitro and in vivo pharmacological effects of Glb against the larval stage of E. granulosus. The in vitro activity was concentration dependent on both protoscoleces and metacestodes. Moreover, Glb combined with the minimum effective concentration of albendazole sulfoxide (ABZSO) was demonstrated to have a greater effect on metacestodes in comparison with each drug alone. Likewise, there was a reduction in the cyst weight after oral administration of Glb to infected mice (5 mg/kg of body weight administered daily for a period of 8 weeks). However, in contrast to in vitro assays, no differences in effectiveness were found between Glb + albendazole (ABZ) combined treatment and Glb monotherapy. Our results also revealed mitochondrial membrane depolarization and an increase in intracellular Ca2+ levels in Glb-treated protoscoleces. In addition, the intracystic drug accumulation and our bioinformatic analysis using the available E. granulosus genome suggest the presence of genes encoding sulfonylurea transporters in the parasite. Our data clearly demonstrated an anti-echinococcal effect of Glb on E. granulosus larval stage. Further studies are needed in order to thoroughly investigate the mechanism involved in the therapeutic response of the parasite to this sulfonylurea.